2015
DOI: 10.2486/indhealth.2014-0214
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual characteristics and night work among nurses

Abstract: Night work has been associated with adverse effects in terms of reproductive health. Specifically, menstruation has been suggested to be negatively impacted by night work, which again may influence fertility. This study investigated whether working nights is related to menstrual characteristics and if there is a relationship between shift work disorder (SWD) and menstruation. The study was cross-sectional, response rate 38%. The sample comprised female nurses who were members of the Norwegian Nurses Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…The differences may be related to different populations and shift schedules. In that study, 56 % were on a three-shift schedule, and 9 % were on a night shift, while almost all nurses experienced a three-shift schedule in the present study [ 25 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The differences may be related to different populations and shift schedules. In that study, 56 % were on a three-shift schedule, and 9 % were on a night shift, while almost all nurses experienced a three-shift schedule in the present study [ 25 ].…”
Section: Discussionmentioning
confidence: 76%
“…Although there are studies that found no association between night work and irregular menstruation or cycle length variation [ 25 ], a systematic review of 16 independent cohorts from 15 studies (a total of 123,403 women) affirmed that shift work could increase the menstrual disruption rate to 16.05 % from 13.05 % in non-shift workers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to sleep during the day are often difficult as their sleep cycles are more susceptible to being disrupted or broken. Because of this, night shift nurses take longer to fall asleep and are unable to enter deep sleep even if they manage to fall asleep, resulting in insufficient and a lack of sleep31 ) , lower sleep quality, and fewer hours of sleep than those of day or evening shift nurses. Amassing sleep debt over time could lead to chronic fatigue, which would ultimately lower one’s alertness and make one more prone to mistakes and accidents32 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review affirmed the effect of shiftwork on menstrual disruption, not only in terms of abnormal cycles, but also spontaneous pregnancy loss [ 26 ]. Another study showed that night work itself did not show a significant association with an irregular menstrual cycle [ 27 ]. Therefore, future research with a detailed study design is warranted to assess the effect of interval time on female health.…”
Section: Discussionmentioning
confidence: 99%